15 Intra & inter-observer reproducibility of quantitative echocardiographic assessment of systemic right ventricular systolic function. (2nd February 2018) - Condie, R; Green, J; Steeds, RP; Hudsmith, L
Abstract : Purpose: Survival in adults with either Transposition of the Great Arteries (TGA) who have undergone an atrial switch (Mustard/Senning) and Congenitally Corrected Transposition of the Great Arteries (ccTGA) might be reduced due to systemic right ventricle (RV) dysfunction. Thus the assessment of systemic RV function is critical in the serial follow-up of these patients. The purpose of this study was to assess the feasibility and reproducibility of standard 2D and 3D transthoracic echocardiographic measurements in these complex adult congenital patients. Methods: All patients (10 ccTGA and 10 TGA) underwent conventional echocardiography. Parameters measured were TAPSE, Tissue Doppler Imaging, 2D Simpson's derived ejection fraction, 3D volumetric ejection fraction and Global Longitudinal Strain. The same BSE accredited GUCH echocardiographer performed all scans, these images were then anonymously viewed by a further 5 BSE accredited echocardiographers who regularly perform ACHD echocardiography. Results: Only 30% of patients were able to have a complete echocardiographic assessment of systolic function, with image quality reported as limited in 80% of patients. Coefficients on intra-observer agreement for all parameters were good (>0.80). Furthermore there was substantial inter-observer agreement for GLS (0.647) and TAPSE (0.632). Both 2D simpsons derived ejection fraction and 3D volumetric ejection fraction showed weak inter-observer reliability (0.167 and 0.215 respectively). Conclusion: GLS and TAPSE are the most reproducible echocardiographic parameters in complex ACHD patients with a systemic right ventricle and should be used for the assessment of systemic right ventricular function in this cohort of congenital patients to optimise reproducibility and reliable serial measurements.